PERAN FINTECH SYARIAH DALAM MENDUKUNG INKLUSI KEUANGAN BAGI PEKERJA MIGRAN INDONESIA DI MALAYSIA: THE ROLE OF ISLAMIC FINTECH IN SUPPORTING FINANCIAL INCLUSION FOR INDONESIAN MIGRANT WORKERS IN MALAYSIA - kusuma, menur (Jurnal Obor Penmas: Pendidikan Luar Sekolah, 2024)
This study investigates the role of Islamic Fintech in promoting financial inclusion for Indonesian Migrant Workers (IMWs) in Malaysia through a qualitative approach. The primary aim of this research is to understand how Islamic Fintech can broaden access to Sharia-compliant financial services for IMWs, who are frequently marginalized by conventional banking systems. In-depth interviews with IMWs and industry experts reveal that Islamic Fintech holds significant potential to enhance their economic well-being by providing financial solutions that adhere to Sharia principles. The findings highlight that Islamic Fintech can bridge gaps left by traditional financial services, offering tools and resources that align with Islamic values and practices. By improving access to these services, Islamic Fintech not only fosters greater financial inclusion but also contributes to the economic stability and empowerment of IMWs in Malaysia. This expanded access is crucial for integrating IMWs into the financial system and supporting their overall economic growth and stability.